Debate of Percutaneous Coronary Intervention versus Coronary Artery Bypass Grafting in a Multimorbidity Patient with Complex Coronary Lesions. (18th May 2020) - Mitsiadis, Sotirios; Miaris, Nikolaos; Dimopoulos, Antonios; Theodosis-Georgilas, Anastasios; Tsiamis, Spyridon; Patsourakos, Nikolaos; Papakonstantinou, Nikolaos; Pisimisis, Evangelos
Abstract : Background . While complete revascularization in coronary artery disease is of high priority, the method of implementation in patients with complex coronary lesions and multiple comorbidities is not directed by published guidelines. Case Presentation . A 53-year-old female with a chronic total occlusion of the right coronary artery and a bifurcation lesion of the left anterior descending artery and the first diagonal branch, presented with non-ST elevation myocardial infarction. Her past medical history concerned thymectomy and prior chest radiation for thymoma, myasthenia gravis, peripheral artery disease, and cervical cancer treated with surgery and radiation. Although SYNTAX score II favored surgical revascularization, the interventional pathway was finally successfully followed. However, it was complicated with vessel perforation and tamponade managed with pericardiocentesis. Conclusion . Comorbidities are not all involved in common risk models and require individualization until more evidence comes to light.